Analisis variasi spasial parameter seismotektonik daerah Sumatera Barat dan sekitarnya dengan menggunakan metoda likelihood - Furqon Dawam Raharjo (Department of Physics – Universitas Negeri Padang UNP, 2016)
West Sumatra is one area with high seismic activity, so that a potentially large and damaging earthquakes. In order to understand the occurrence of large earthquakes and damage need to know the local stress conditions and the level of seismic activity by analyzing seismotectonic parameters (a-value) and (b-value). Seismotectonic parameters low (a-value) and (b-value) can be interpreted with a low level of seismic activity and the condition of local rock high stress, otherwise the high (a-value) and (b-value). This study by using a distribution relationship with the frequency-magnitude earthquake with likelihood method and then analyzed by using software ZMAP shaped graphic user interface (GUI) -based matlab. The data used in this study taken from the USGS and BMKG with the observation period 1960 - 2015, the parameters of earthquakes with shallow depths (h) <60 km and intermediate (h) 60-350 km with a magnitude of earthquakes (M> 4.0 SR). The results show the spatial variation seismotectonic parameters low (a-value) and (b-value) at shallow depths (h) <60 km observedat southern of Nias Island, along the west coast of northern Sumatra, active faults zone north Sumatra, around the Mentawai islands and parts of Sumatra active fault zone precisely in the area of Solok and South Solok. While at intermediate depths (h) 60-350 km observed at southeastern of Batu island and the west of Padang. Thus these areas a potentially large and damaging earthquakes